“Candidatus Trichorickettsia mobilis”, a Rickettsiales bacterium, can be transiently transferred from the unicellular eukaryote Paramecium to the planarian Dugesia japonica - Letizia Modeo (PeerJ, 2020)
Most of the microorganisms responsible for vector-borne diseases (VBD) have hematophagous arthropods as vector/reservoir. Recently, many new species of microorganisms phylogenetically related to agents of VBD were found in a variety of aquatic eukaryotic hosts; in particular, numerous new bacterial species related to the genus Rickettsia (Alphaproteobacteria, Rickettsiales) were discovered in protist ciliates and other unicellular eukaryotes. Although their pathogenicity for humans and terrestrial animals is not known, several indirect indications exist that these bacteria might act as etiological agents of possible VBD of aquatic organisms, with protists as vectors. In the present study, a novel strain of the Rickettsia-Like Organism (RLO) endosymbiont “Candidatus (Ca.) Trichorickettsia mobilis” was identified in the macronucleus of the ciliate Paramecium multimicronucleatum. We performed transfection experiments of this RLO to planarians (Dugesia japonica) per os. Indeed, the latter is a widely used model system for studying bacteria pathogenic to humans and other Metazoa. In transfection experiments, homogenized paramecia were added to food of antibiotic-treated planarians. Treated and non-treated (i.e. control) planarians were investigated at day 1, 3, and 7 after feeding for endosymbiont presence by means of PCR and ultrastructural analyses. Obtained results were fully concordant and suggest that this RLO endosymbiont can be transiently transferred from ciliates to metazoans, being detected up to day 7 in treated planarians’ enterocytes. Our findings might offer insights into the potential role of ciliates or other protists as putative vectors for diseases caused by Rickettsiales or other RLOs and occurring in fish farms or in the wild.